Di (2-ethylhexyl) Phthalate Exposure Impairs the microRNAs Expression Profile During Primordial Follicle Assembly - Zhang, Jiao-Na; Zhang, Rui-Qian; Liu, Jing-Cai; Li, Lan; Shen, Wei; Sun, Xiao-Feng (Frontiers in Endocrinology, 2019)
This research was performed to estimate the potential effects of Di (2‑ethylhexyl) phthalate (DEHP) on changes of ovarian miRNA expression profile during mouse primordial follicle assembly using miRNAs-seq analysis. The ovaries of newborn mice were collected and in vitro cultured with different concentration of DEHP for 72 hours. Then they were prepared for miRNAs-seq analysis. The results indicated that DEHP exposure altered ovarian miRNA expression profile of newborn mice. Eighteen differentially expressed miRNAs were screened after 100 μM DEHP exposure. The target mRNAs of differentially expressed miRNAs were predicted and further analyzed through gene ontology (GO) enrichment analysis and pathway enrichment analysis. Our results showed that the differentially expressed miRNAs from DEHP exposure can regulate ovarian development by targeting mRNAs involved in MAPK, mTOR, FoxO signaling pathways. Three miRNAs of miR-32-5p, miR-19a-3p and miR-141-3p were randomly selected from the differentially expressed miRNAs to quantify their expression level by miRNA qRT-PCR. The results of qRT-PCR and miRNA-seq were consistent. Considering one of its target gene PTEN of miR-19a-3p and the decreased level of pAKT and increased Bax/Bcl-2 under DEHP exposure, we speculated that the altered expression of miR-19a-3p by DEHP exposure affected mouse primordial follicle assembly via PI3K/AKT1/mTOR signaling pathway. Epigenetic changes are one of the most important targets of toxicant exposure. The effects of DEHP exposure on microRNA (one of the epigenetic regulators) expression profile were uncovered to enrich the research on relationship of epigenetics and toxicant exposure.